The SAGE handbook of social media research methods - Sloan, Luke; Quan-Haase, Anabel
With coverage of the entire research process in social media, data collection and analysis on specific platforms, and innovative developments in the field, this handbook is the ultimate resource for those looking to tackle the challenges that come with doing research in this sphere.